2014
DOI: 10.1039/c4dt02421d
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism dependent light induced spin transition

Abstract: A photomagnetic study of orthorhombic and tetragonal low spin polymorphs of compound [Fe(L)2](BF4)2 revealed different properties and thermal stability of their metastable high spin states. Furthermore, the reversible thermally induced phase/spin transition between low spin and high spin orthorhombic phases was studied by variable temperature UV/VIS spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
(6 reference statements)
0
20
0
Order By: Relevance
“…[30,44] While it occurs at a similar temperature to the compounds in this work, the spin-transition in 4 is more cooperative with a 8 K hysteresis loop, reflecting the involvement of the phase change in its SCO. While it is difficult to draw further comparison between 1-3 and 4, this emphasizes the structural complexity of the [Fe (bpp)2] 2+ system in this particular lattice type.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…[30,44] While it occurs at a similar temperature to the compounds in this work, the spin-transition in 4 is more cooperative with a 8 K hysteresis loop, reflecting the involvement of the phase change in its SCO. While it is difficult to draw further comparison between 1-3 and 4, this emphasizes the structural complexity of the [Fe (bpp)2] 2+ system in this particular lattice type.…”
Section: Resultsmentioning
confidence: 91%
“…For all complexes, a drastic increase in the magnetic signal under green light irradiation was observed at 10 K. However, unusually for [Fe(bpp)2] 2+ derivatives, [7,20,[28][29][30] the photoconversion efficiency was not quantitative. The maximum MT values indicate photoconversion efficiencies of 70 % (for 1), 57 % (2) and 60 % (3).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Beyond SCO coordination polymers, discrete molecular SCO species incorporating imidazole- [16], pyrazole- [17] or pyridine-type [18,19,20] ligands have been shown to exhibit room temperature transitions with moderate thermal hysteresis widths [21]. Within the last decade, the iron(II) complexes with tridentate bis(pyrazole)pyridine [22,23,24,25,26,27,28,29,30,31,32,33] ligands have drawn increasing of attention to the field of SCO complexes. It has been shown that the modification of the ligand skeleton by substituents on the pyridine [23,24,25,26] or pyrazole [27] moiety leads to a fine-tuning of SCO properties.…”
Section: Introductionmentioning
confidence: 99%
“…Within the last decade, the iron(II) complexes with tridentate bis(pyrazole)pyridine [22,23,24,25,26,27,28,29,30,31,32,33] ligands have drawn increasing of attention to the field of SCO complexes. It has been shown that the modification of the ligand skeleton by substituents on the pyridine [23,24,25,26] or pyrazole [27] moiety leads to a fine-tuning of SCO properties. This is in fact a powerful tool for the synthesis of room temperature SCO compounds with anchoring functional substituents, which are tailor-made for the fabrication of hybrid materials, i.e., SCO surfaces [28] or SCO nanoparticles [29].…”
Section: Introductionmentioning
confidence: 99%